(untitled) (Research, Society and Development, 2020)
This study aims to analyze the accounting control practices of microentrepreneurs who are located in the city of Rondon do Pará. It is verified that the sale of street food is a growing activity, and that it has been developed in the municipality with Food Trucks if highlighting in the card line, because they offer fast food, of quality and with accessible values. For this research, questionnaires were applied with open and closed questions, in a sample of 10 microentrepreneurs located in the urban route of BR 222 of that city. Aspects related to accounting and financial controls are analyzed, such as cash flow, inventory, working capital, sales volume, supplier, raw material and sales price, verifying the profile of these entrepreneurs and the level of education. The study concludes that there is a very small amount of MEI that constitute and adopt these management instruments, proceeding to control in a rudimentary way. It is noticed that this fact is linked to the lack of guidance and assistance from professionals in the accounting area. On the other hand, it is noticeable the interest of this group in acquiring knowledge on the subject and that they have the desire to participate in courses offered by institutions.